Aeromicrobium chenweiae sp. nov. and Aeromicrobium yanjiei sp. nov., isolated from Tibetan antelope (Pantholops hodgsonii) and plateau pika (Ochotona curzoniae), respectively. Issue 8 (21st August 2020) - Li, Junqin; Lei, Wenjing; Yang, Jing; Lu, Shan; Jin, Dong; Lai, Xin-He; Zhang, Sihui; Cheng, Yanpeng; Mi, Fei; Huang, Yuyuan; Pu, Ji; Dong, Kui; et al.
Abstract : Four novel strains (592 T, S592, MF47 T and SMF47) were isolated from Tibetan antelopes ( Pantholops hodgsonii ) and plateau pikas ( Ochotona curzoniae ), respectively. The cells were aerobic, non-motile, Gram-stain- and catalase-positive, rod-shaped bacteria. The 16S rRNA gene sequences of the four strains showed highest similarities to Aeromicrobium fastidiosum DSM 10552 T (98.1, 98.6, 98.7 and 98.7 %, respectively), and the phylogenetic analyses based on 16S rRNA gene and genomic sequences indicated that strains 592 T and MF47 T represent two novel species. The four isolates produced acid from l -rhamnose, d -xylose and cellobiose, but were unable to reduce nitrate. The DNA G+C contents of strains 592 T and MF47 T were 70.3 and 69.8 mol%, respectively. The digital DNA–DNA hybridization value between strains 592 T and MF47 T was 32.6 %, lower than the threshold of 70 %, indicating they belong to different species. The four strains' genomes displayed less than 24.6 % DNA–DNA relatedness with all available genomes of the genus Aeromicrobium in the NCBI database, including Aeromicrobium fastidiosum NBRC 14897 T and Aeromicrobium ginsengisoli JCM 14732 T . The major fatty acids of the four strains were C18 : 1 ω9 c and C18 : 0 10-methyl, and the main polar lipids were diphosphatidylglycerol, phosphatidylglycerol and phosphatidylinositol. The predominant respiratory quinones were MK-9(H4 ) and MK-8(H4 ). The cell-wall peptidoglycan contained ll -diaminopimelic acid. Based on these genotypic, phenotypic and biochemical analyses, it is proposed that the four unidentified bacteria be classified as two novel species, Aeromicrobium chenweiae sp. nov. and Aeromicrobium yanjiei sp. nov. The type strains are 592 T (=CGMCC1.16526 T =DSM 106289 T ) and MF47 T (=CGMCC 1.17444 T =JCM 33790 T ), respectively.